Study Literature: Role of Secretome Mesenchymal Stem Cell as Innovation in Burn Treatment - Desti Wulandari; Marlina Marlina; Rahmi Novita (JURNAL PROTEKSI KESEHATAN, 2023)
The purpose of this review was to determine the role of MSCs in burn management. Scientific publication databases such as Researchgate, Google Scholar, ScienceDirect, and Pubmed were used for literature searches. [(Secretome, Mesenchymal stem cell Adipose Tissue, Umbilical Cord, Bone Marrow) AND (Burn wound OR wound healing OR burn injury OR thermal injury)] are the keywords used. In ten studies, rats, mice, and humans were used as research subjects in randomized clinical trials to conduct synthetic analyses. MSC therapy involves the use of bone marrow, cord blood, and adipose tissue. MSC therapy heals burns by suppressing the inflammatory response and oxidative stress, stimulating angiogenesis, and causing closure and repair (remodeling). MSC therapy has also been shown to reduce scarring and contracture formation.